Analysis of YouTube Use Pattern among Farmers for Agro-advisory - Tambade, L.R.; Gonjari, P.A.; Singh, Lakhan (Indian Journal of Extension Education, 2019)
YouTube is the most popular social media platform for young farmers and agricultural professionals for seeking information related to agricultural innovations, upcoming technologies and specialized skills, as evident from number of videos uploaded by different users. YouTube is the 2nd largest search engine and 3rd most visited site on the web. Almost 94 per cent farmers use mobile phone, especially in developed countries. Farmers are more likely to be found on YouTube in the early morning hours or evening. KVK, Solapur designed and developed YouTube channel by the name “LRT Farm Advise” on March, 21 2015. Developed 3-5 minutes videos as per the demand of farming community based on problem and uploaded it. The short videos of production, protection and innovations were uploaded, out of that five point technology of Red gram production got highest response. The majority (95.10%) YouTube subscribers belong to young (25 to 34 years) category. It was observed that 2,362 viewers seen the videos more than 3633 minutes within last 28 days. Also more than 5,25,600 minutes view time since first upload. It is inferred that YouTube channel helps to improve knowledge of farming, enhance adoption of innovation & improved technologies helps to increase productivity and farm income.
Keywords: Advisory; Social media; Subscribers; Views; Watch time; YouTube